The experience of women in the climate period: integrative review (Research, Society and Development, 2021)
Climacteric is characterized according to a stage of change between the reproductive and non-reproductive phases of the woman's life cycle, in a non-pathological way. Objective: to understand how women experience the climacteric and to know the repercussions of the climacteric in their lives. This is an integrative literature review based on the PICo strategy, carried out in the database of Lilacs - Latin American and Caribbean Literature in Health Science and Bdenf - Database in Nursing with the descriptors Mesh, woman, experience, climacteric, change of life. 77 studies were retrieved after inclusion and exclusion criteria, obtaining 25 articles that made up the final sample. Three categories were constructed: Experiencing the signs and symptoms of menopause; The repercussions of menopause in women's social life and the repercussions of menopause on women's psychological aspects. It was shown that each woman experiences menopause in a unique way, as well as the symptoms that have a different impact on each woman's life.